Troilus and Cressida: Classical Past and Medieval Heritage - Piero Boitani (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2024)
Among Shakespeare’s ‘classical’ plays, Troilus and Cressida occupies an especially problematic place. The play is, to sum it up in an approximate formula, suspended between Homer and Chaucer, two authors and two styles not easy to reconcile with each other. Two scenes in particular in the play are characterized by a conflict between sources which entirely changes both the classical and the medieval features of Troilus and Cressida. This brief essay offers a reading of Act III, scene ii and a handful of lines in Act V, scene ix, drawing on Piero Boitani’s lifelong work on the Troilus and Cressida story.